Comparative treatment costs for patients with acute myocardial infarction between Finland and Norway - Tor Iversen; Unto Häkkinen (University of Oslo, 2019)
Previous studies on patients with acute myocardial infarction have found that Finland has higher hospital costs per patient than Norway for the first hospital episode (HEP), while Norway has higher costs   during the first year after the initial admission. In this paper, we analyze the variation in treatment costs between Finland and Norway in detail by introducing novel explanatory variables. We find that the distance from the patient's home to the hospital increases hospital costs at a declining scale and one-year hospital costs are higher for low-income patients. The higher one-year hospital costs in Norway are accompanied by a comparatively lower mortality rate. While for HEP, the introduction of new explanatory variables does not explain the greater costs in Finland compared with Norway, for one-year costs, the additional variables explain the greater one-year costs in Norway compared to Finland. Published: Online January 2019. In print January 2019.